Jointly Optimal Sales Commissions for Nonincome Maximizing Sales Forces - Weinberg, Charles B. (Management Science, 1978)
In a multiproduct sales force, it has previously been shown that a commission structure based on equal fractions of each product's realized gross margin is jointly optimal if the sales force's goal is to maximize (expected) income and products are independent. Jointly optimal means that the sales force, which is presumed to be best able to estimate customer response to sales force activities, will simultaneously act to optimize its own objective and maximize corporate earnings. In this paper, it is shown that an equal gross margin commission system is also jointly optimal when products are interdependent and when the sales force does not have a goal of income maximization but has other objectives, such as minimizing time to reach a certain income goal or trading off time against money. Further, not all salespeople are required to have the same objective. For income maximizers an approach requiring less stringent assumptions than previously employed to show joint optimality is developed.